2021
DOI: 10.1002/casp.2514
|View full text |Cite
|
Sign up to set email alerts
|

Caregiving burden and depressive symptoms among ultra‐orthodox Jews: The moderating role of sense of community

Abstract: Individuals who care for aging parents or relatives often experience caregiving burden, which is associated with various negative psychological outcomes. During the current COVID-19 pandemic, the conflict between caring for older relatives and taking the necessary personal precautions against infection may be exacerbated among individuals who belong to social groups, which perceive caring for others as an indispensable cultural construct. Accordingly, the current study examined whether feeling a part of one's … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Some focus on interventions designed to build SOC and belonging in the midst of disruptions to social interactions (Dougherty & Dougherty, 2020; Frei‐Landau, 2020); others on exploring SOC's relation with COVID‐19 outcomes. For example, SOC has been shown to moderate negative mental health symptoms related to caregiver burdens (Maytles et al, 2021) and moderate the increased risk of elder abuse during the pandemic (E. S. Chang & Levy, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Some focus on interventions designed to build SOC and belonging in the midst of disruptions to social interactions (Dougherty & Dougherty, 2020; Frei‐Landau, 2020); others on exploring SOC's relation with COVID‐19 outcomes. For example, SOC has been shown to moderate negative mental health symptoms related to caregiver burdens (Maytles et al, 2021) and moderate the increased risk of elder abuse during the pandemic (E. S. Chang & Levy, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The importance of SOC in the Ultra‐Orthodox community can be seen as helping to deal with difficulty and burden, especially in the COVID‐19 era (Maytles et al, 2021). Recent studies have demonstrated the positive relationship between MIL and SWL (Arslan & Yıldırım, 2021; Yıldırım et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The close ties community members have with each other ensure that all are obliged to provide support to those who need it. Moreover, Maytles et al (2021) demonstrated that in this population, SOC was associated with reduced depressive symptoms associated with caring for older family and community members during COVID‐19. However, as previously stated, the mechanisms through which SOC affects life satisfaction during COVID‐19 remain relatively unclear.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…In a longitudinal survey study, Luchetti et al (2020) found that people reported increased support after the pandemic compared to before. All these perceptions and altruistic activities may help to sustain and enhance people’s communal satisfaction and well-being (Gayatri & Irawaty, 2022; Jiang & Fung, 2022; Mannarini et al, 2022; Maytles et al, 2021).…”
Section: Life Satisfaction During the Pandemic: The Mental Health Domainmentioning
confidence: 99%